1998
DOI: 10.1074/jbc.273.40.26171
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glutathione Peroxidase in Bovine Eye

Abstract: Bovine ciliary body contains a selenium-independent glutathione peroxidase (GPX) with a molecular mass of about 100 kDa that is composed of four identical subunits and exhibits no glutathione S-transferase activity. In this study, we isolated cDNA clones and determined the nucleotide sequence to deduce the primary structure of the enzyme. The cDNA contained 672 base pairs encoding a polypeptide with an estimated molecular mass of 25,064 Da. Translation of bovine ciliary mRNA produced a protein which was immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 32 publications
2
27
2
Order By: Relevance
“…Initial studies indicated that GSH could function as a reductant with 1-cysPrx isolated from bovine eye (20) or rat olfactory epithelium (21), although the latter result subsequently could not be reproduced (22). Studies with recombinant protein also have been inconclusive because GSH has been effective in some studies (7,23) but not in others (6). All reports agree that thioredoxin, a physiological reductant for other members of the peroxiredoxin family, does not reduce 1-cysPrx (7,24).…”
Section: Resultsmentioning
confidence: 83%
“…Initial studies indicated that GSH could function as a reductant with 1-cysPrx isolated from bovine eye (20) or rat olfactory epithelium (21), although the latter result subsequently could not be reproduced (22). Studies with recombinant protein also have been inconclusive because GSH has been effective in some studies (7,23) but not in others (6). All reports agree that thioredoxin, a physiological reductant for other members of the peroxiredoxin family, does not reduce 1-cysPrx (7,24).…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, based upon the cDNA sequence, this protein belongs to the thioredoxin peroxidase, or peroxiredoxin, family although with only one instead of the usual two conserved cysteine residues and thus has been called 1-Cys peroxiredoxin (5). The nomenclature is further confusing since the enzyme does not utilize thioredoxin (4,5), but rather functions as a GSH peroxidase (3,4). Although the cDNA sequence of aiPLA 2 (1) is identical to that of NSGPx (4), the presence of both activities up to the present has not been confirmed in the same peptide.…”
mentioning
confidence: 99%
“…Evidence has emerged that a lysosomal-type Ca 2Ï© -independent phospholipase A 2 with acidic pH optimum (aiPLA 2 ) 1 (1,2) and a non-selenium glutathione peroxidase without glutathione S-tranferase activity (NSGPx) (3,4) are the same enzyme, based upon their identical cDNA sequence. Furthermore, based upon the cDNA sequence, this protein belongs to the thioredoxin peroxidase, or peroxiredoxin, family although with only one instead of the usual two conserved cysteine residues and thus has been called 1-Cys peroxiredoxin (5).…”
mentioning
confidence: 99%
“…By contrast, 1-cys peroxiredoxin (1-cysPrx or Prx VI) † has a single conserved cysteine (5) and does not use thioredoxin as reductant (5, 6). This peroxiredoxin is expressed in all tissues but at particularly high levels in brain, eye, testes, and lung (2,7,8). Expression of 1-cysPrx protein or mRNA is decreased in a mouse that is susceptible to experimental atherosclerosis (9) and is elevated in brains of patients with Parkinsonian dementia (10), sporadic Creutzfeldt-Jacob disease (11), and Pick disease (12), in lungs from newborns (13), in malignant mesothelioma (14), in the healing edge of skin wounds (15), and in experimental cellular premature senescence (16).…”
mentioning
confidence: 99%